2016
DOI: 10.1111/imm.12571
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A neutralization alleviated ocular neovascularization by promoting M2 and mitigating M1 macrophage polarization

Abstract: SummaryNeovascularization (NV), as a cardinal complication of several ocular diseases, has been intensively studied, and research has shown its close association with inflammation and immune cells. In the present study, the role of interleukin-17A (IL-17A) in angiogenesis in the process of ocular NV both in vivo and in vitro was investigated. Also, a paracrine role of IL-17A was demonstrated in the crosstalk between endothelial cells and macrophages in angiogenesis. In the retinas of mice with retinopathy of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 42 publications
(81 reference statements)
2
70
0
Order By: Relevance
“…Elimination of macrophage recruitment via Ccr2 knockout diminished the development of AMD disease phenotypes after CEP-MSA injection, demonstrating a role of M1-like inflammatory macrophages in the development of early AMD disease phenotypes (RPE dysfunction and loss) [85]. Others have demonstrated a possible role of M1-like macrophages in mediating the later phenotype of neovascularization [86]. Specifically, in both laser-induced CNV and an oxygen-induced model of retinopathy of prematurity, removal of Il17a by genetic knockout or neutralizing antibody reduced the M1 population and increased the M2 population, and caused reduced neovascularization in both disease models relative to controls.…”
Section: Conflicting Roles Of Macrophage Populations In Amdmentioning
confidence: 99%
“…Elimination of macrophage recruitment via Ccr2 knockout diminished the development of AMD disease phenotypes after CEP-MSA injection, demonstrating a role of M1-like inflammatory macrophages in the development of early AMD disease phenotypes (RPE dysfunction and loss) [85]. Others have demonstrated a possible role of M1-like macrophages in mediating the later phenotype of neovascularization [86]. Specifically, in both laser-induced CNV and an oxygen-induced model of retinopathy of prematurity, removal of Il17a by genetic knockout or neutralizing antibody reduced the M1 population and increased the M2 population, and caused reduced neovascularization in both disease models relative to controls.…”
Section: Conflicting Roles Of Macrophage Populations In Amdmentioning
confidence: 99%
“…Conditions of RPE degeneration, including age-related macular degeneration (AMD) and retinitis pigmentosa, are believed to involve dysregulated immune responses (12,13). Although extensive studies have been performed to demonstrate how activated immune cells and complement proteins contribute to the inflammatory and angiogenic responses in the outer retina (14)(15)(16)(17), it has not been established whether the innate immune cells of the choroid can exert protective effects against RPE injury.…”
mentioning
confidence: 99%
“…A number of studies have reported that different cytokines, such as IL-10, IL-12, IFN-γ, IL-17, IL-18 and IL-33, may play a role in the pathogenesis of CNV [33][34][35][36][37]. The pro-and anti-angiogenic effects of the cytokines relevant to Th1, Th2 and Th17 cells, participate in a complicated immunological network [38].…”
Section: Discussionmentioning
confidence: 99%